The Dual Impact of Social Media Use in the Workplace on Employee Behavior: Cyberloafing Perspective - Kilic, Merve; Muceldili, Busra (LUMEN PUBLISHING HOUSE, 2025)
The increasing alignment of internet-based technologies into business processes has transformed the contemporary work environment, influencing employees' use of digital devices during working hours. While such usage facilitates professional tasks, it also encompasses personal activities known as cyberloafing. This study investigates the relationships among workplace ostracism, challenge stressors, cyberloafing behaviour, and psychological detachment is based on the of Conservation of Resources (COR) theory. A structured questionnaire assessing the relevant variables was administered to a sample of 257 full-time employees. The findings showed a significant positive association between workplace ostracism and cyberloafing, however, challenge stressors did not significantly predict cyberloafing behaviour Moreover, cyberloafing was positively related to psychological detachment. While no significant relationship was found between ostracism and psychological detachment, challenge stressors showed a significant negative association with psychological detachment. These results contribute to understanding how social and job-related stressors differentially impact employees' cyberloafing tendencies and psychological detachment from work. The study generates theoretical insights and practical implications for researchers and practitioners aiming to address workplace behaviours in digitalized organizational settings.
Keywords: workplace ostracism; challenge stressors; cyberloafing; psychological detachment; conservation of resources theory; OSTRACISM; SELF; JOB; CONSERVATION; VALIDATION; RESOURCES; STRESS; Education & Educational Research